2021
DOI: 10.1111/ijcp.14428
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of hospitalised older patients with chronic kidney disease and COVID‐19: A multicenter nationwide controlled study

Abstract: Objective Older adults with co‐morbidities have been reported to be at higher risk for adverse outcomes of coronavirus disease 2019 (COVID‐19). The characteristics of COVID‐19 in older patients and its clinical outcomes in different kidney disease groups are not well known. Methods Data were retrieved from a national multicentric database supported by Turkish Society of Nephrology, which consists of retrospectively collected data between 17 April 2020 and 31 December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…The presence of kidney disease is a risk factor for poor outcomes of severe infections such as COVID-19 (32)(33)(34)(35)(36), and infections are the second common cause of death in patients with CKD (37)(38)(39). This has been attributed to secondary immunodeficiency (SIDKD) to which many of the consequences of kidney disease contribute (8).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of kidney disease is a risk factor for poor outcomes of severe infections such as COVID-19 (32)(33)(34)(35)(36), and infections are the second common cause of death in patients with CKD (37)(38)(39). This has been attributed to secondary immunodeficiency (SIDKD) to which many of the consequences of kidney disease contribute (8).…”
Section: Discussionmentioning
confidence: 99%
“…Patients presenting with pre-existing kidney conditions, such as chronic kidney disease (CKD), including both end-stage kidney disease (ESKD) and pre-dialysis CKD, are also at greater risk for poor outcomes from COVID-19. Baseline kidney disease has been consistently found to be an independent risk factor for severe disease or mortality from COVID-19, even when adjusting for confounding risk factors, such as underlying diabetes, hypertension, and cardiovascular disease [18,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Despite the clear connection between baseline kidney function and COVID-19 severity, far fewer data have been published to elucidate the effect of survival from COVID-19 on subsequent long-term kidney function, but four recent analyses of large datasets suggest a link [55][56][57][58].…”
Section: Relationship Between Covid-19 Pre-existing Ckd and Risk Of F...mentioning
confidence: 99%
“…A large study from Turkey analyzed 1,210 patients with COVID-19 and found that intensive care unit (ICU) admission and the mortality rate were higher in patients with CKD and HD patients compared to those without kidney disease [ 9 ]. Another study from Turkey analyzed 879 CKD and control patients, 68.8% of them were more than 65 years of age and found out that severe-critical disease, ICU admission, and in-hospital mortality were found to be more frequent in the older group regardless of demographic parameters, comorbidities, clinical, and laboratory data on presentation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%